2020
DOI: 10.3390/socsci9080138
|View full text |Cite
|
Sign up to set email alerts
|

Dialogic Feminist Gatherings: Impact of the Preventive Socialization of Gender-Based Violence on Adolescent Girls in Out-of-Home Care

Abstract: Gender-based violence is a social scourge with an increasing incidence at younger ages. Many studies have focused on finding effective solutions for overcoming this problem; however, few studies have analyzed the contribution of interactive learning environments to gender-based violence prevention. This article attempts to fill this gap by showing the impact of Dialogic Feminist Gatherings on the preventive socialization against gender-based violence toward adolescent girls (aged 15–18) who are in out-of-home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
(50 reference statements)
2
21
0
1
Order By: Relevance
“…For instance, participants in the research confirmed having fewer problems with their weight, some of them have decided to not smoke, and there are other interviewees who are happier now than before being involved in Men in Dialogue. Concerning the shaping of conversations and interactions addressing favorable practices [ 56 , 57 ], the fieldwork illustrates the importance of establishing relationships, framed on support and trust that foster healthy practices and reinforce emotional well-being. Thus, the results show the interconnection between this emotional well-being and men’s physical health.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, participants in the research confirmed having fewer problems with their weight, some of them have decided to not smoke, and there are other interviewees who are happier now than before being involved in Men in Dialogue. Concerning the shaping of conversations and interactions addressing favorable practices [ 56 , 57 ], the fieldwork illustrates the importance of establishing relationships, framed on support and trust that foster healthy practices and reinforce emotional well-being. Thus, the results show the interconnection between this emotional well-being and men’s physical health.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we have shared a program of seven interventions framed by the research line of preventive socialization of gender violence that were applied as part of the MEMO4LOVE Project in Spain. We explain it here as the program has already proven to be successful in generating transformative changes in dimensions that are involved in gender violence victimization, as already reported and published in indexed scientific journals [28] , [33] , [34] .…”
Section: Discussionmentioning
confidence: 94%
“…This article is not focused on the impact of the program, which is being already reported in other scientific articles [28] ; thus the research data collected throughout the research project is not shared here. We share the program of interventions given the efficacy that actions grounded in the scientific evidence from the research line on preventive socialization of gender violence have already demonstrated [33] , [34] , including this program. Other publications [28] ; have shown that this exact program of interventions contributed to raising the participant adolescents' consciousness regarding the presence of the dominant coercive discourse in their life, aided their better understanding of sexual-affective behaviors, thoughts and feelings, and supported the modification of sexual preferences in some female adolescents in a direction of rejecting violent males.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the individual level, neuroscience has also evidenced how kindness fosters a healthy brain (Galante et al 2014) and leads to relationships characterized by pleasure and desire (Racionero-Plaza et al 2020). When Racionero-Plaza and colleagues studied a specific intervention focused on supporting the free reconstruction of mental and affective models of attractiveness, they found dialogue to be an essential tool for achieving this aim (Salceda et al 2020).…”
Section: Introductionmentioning
confidence: 99%